2020
DOI: 10.1088/1742-6596/1430/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of gram-negative bacteria of Bali cattle with repeat breeding cases on East Lombok, West Nusa Tenggara Province

Abstract: The target of self-sufficiency in 2017 has been launched by President of Republic Indonesian. The province of West Nusa Tenggara (NTB) with “Bumi Sejuta Sapi (BSS) and UPSUS SIWAB Program has been recognized as the key site for production and supply of meat and cattle for all of part of Indonesia. One of the classic problems that led to the lack of that program is the repeat breeder in cattle that associated with the presence of Gram-negative bacteria in the reproductive tract. The purpose of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
1
2
0
1
Order By: Relevance
“…These results are close to the results of the previous study, which stated that 33.33% (3/10) of E. coli were found in 10 isolates of Gram-negative bacteria in repeat breeder cattle in Aceh (9). Research on Bali cattle in Lombok also documented the presence of E. coli, Citrobacter freundii, and Proteus vulgaris bacteria in 4 samples of reproductive tract fluid from Bali cattle that experienced repeat breeder (18).…”
Section: Discussionsupporting
confidence: 89%
“…These results are close to the results of the previous study, which stated that 33.33% (3/10) of E. coli were found in 10 isolates of Gram-negative bacteria in repeat breeder cattle in Aceh (9). Research on Bali cattle in Lombok also documented the presence of E. coli, Citrobacter freundii, and Proteus vulgaris bacteria in 4 samples of reproductive tract fluid from Bali cattle that experienced repeat breeder (18).…”
Section: Discussionsupporting
confidence: 89%
“…E. coli in methyl red and indole tests showed positive results and negative reactions for the Voges-Proskauer test and citrate, the results of these tests that distinguish them from other digestive tract bacteria (Cornelissen et al, 2013). This statement is corroborated by the research of Aminuddi et al (2020) who documented that E.coli isolated from the reproductive tract of Bali cattle ferment carbohydrates and produce gas. E. coli with the same biochemical results have also been isolated from anal swabs in bats, where E. coli ferments glucose and lactose (Kholik et al, 2019).…”
Section: E Coli Colonies Grown In Eosin Methylenementioning
confidence: 58%
“…Escherichia coli is used as an indicator because the AMR profile of E. coli almost reflects the use of antimicrobials in animals for food production (EFSA, 2011). Previous research data on the island of Lombok documented that E. coli had been isolated from Bali cattle with reproductive disorders in Central Lombok (Aminuddi et al, 2020). Gunawan et al (2018) have reported that among 94.4% of E. coli were isolated from 20 samples of Bali cattle feces in smallholder farms in Central Lombok, 61% of E. coli samples were resistant to Erythromycin and Tetracycline, and 16.7% of E. coli samples were resistant to Ciprofloxacin.…”
Section: Introductionmentioning
confidence: 99%
“…Ganguan penyakit sebagai akibat adanya infestasi penyakit yang dapat menggangu kesehatan. Peningkatan produksi dan reproduksi akan optimal, bila secara simultan disertai penyediaan pakan yang memadai dan pengendalian penyakit yang efektif [9]. Diantara sekian banyak penyakit hewan di Indonesia, penyakit parasit masih kurang mendapat perhatian dari para peternak [10].…”
Section: Pendahuluanunclassified